Green roofs dissemination regarding their potential contribution in addressing the UHI effect - Klimek, Andrzej; Gulma, Sadiq; Suhanova, Dina; Agbonlahor, Mure; Jung-Waclik, Sabine; Ziogou, Isidoros; Michopoulos, Apostolos; Zachariadis, Theodoros (My University, 2019)
The article aims at summarising the state of the art in the efforts of researchers and innovators to find viable solutions to mitigate the urban heat island (UHI) effect. This effect is loosely connected with the greenhouse effect, however, it certainly creates a severe negative synergy together with it. As green roofs are a well-known answer how to address the UHI effect, the ways how to make their massive and global deployment convenient are discussed. Initially, the differences and similarities between urbanisation in developed and developing countries are described. Then the paper depicts solutions, especially synergic ones, for making the dissemination of green roofs viable, such as rainwater and energy harvesting or urban agriculture. Then the authors conclude that retrofitting the existing roofs is the only method for reaching the desired scale and discuss available business models necessary for introducing the prosumer approach to the retrofitting.
Keywords: Efficiency of FWE resources; Green roofs; Prosumer model; Urban Heat Islands; Urban regeneration